2018
DOI: 10.1590/s1983-41952018000300007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the chloride penetration and service life of self-healing concretes activated by crystalline catalyst

Abstract: The main cause of concrete structures deterioration is related to the resistance against the penetration of aggressive agents. Aiming at increase the impermeability and reduce the diffusivity of concrete elements, making it less susceptible to the ingress of chloride ions, the use of crystalline catalyst emerges as a good alternative. Its mechanism of autogenous healing enhances the natural pore-filling process of concrete. The aim of this study is to investigate the influence of the use of crystalline catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
6
0
1
Order By: Relevance
“…Crystalline admixture resulted in a low flow reduction when compared to the reference concrete (REF). Helene et al [33] reported that concretes made with or without the crystalline catalyst achieved similar slump values. Differently, Azarsa et al [12] and Oliveira et al [41] observed a decrease in a concrete slump value with the crystalline admixture addition.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Crystalline admixture resulted in a low flow reduction when compared to the reference concrete (REF). Helene et al [33] reported that concretes made with or without the crystalline catalyst achieved similar slump values. Differently, Azarsa et al [12] and Oliveira et al [41] observed a decrease in a concrete slump value with the crystalline admixture addition.…”
Section: Resultsmentioning
confidence: 98%
“…Cylindrical specimens were cast (100 mm diameter and 200 mm height) and after 48 h in molds, the specimens were demolded and stored for 5 days in a wet chamber (22 °C and relative humidity of 95%). Some of the specimens had a crack induction process at 7 days, which is commonly used to test the healing efficiency [22,25,32,33]. After the cracking process, all the specimens were immersed in water until testing age.…”
Section: Methodsmentioning
confidence: 99%
“…For the age of 91 days, it can be noted that the concretes containing the crystalline admixtures showed less resistance in the compressive test when compared to the reference. Likewise, Helene et al [41] demonstrated little contribution of crystalline admixtures to concrete compressive strength, for the same w/c ratios, at the age of 91 days. Munn, Chang, and Kao [42] found that the addition of 0.8% and 1.2% crystalline admixtures did not significantly increase the compressive strength of concretes made with ordinary cement, but found an increase in strength at 28 and 91 days for concretes produced with pozzolanic cement and the addition 1.2% crystalline admixtures.…”
Section: Compressive Strengthmentioning
confidence: 91%
“…As a consequence of this, the service life of steelreinforced concrete slabs in marine environments could amount to 60-94 years, as opposed to 7 years for ordinary cracked concrete. Another work with crystalline admixture (2% of cement weight) in concrete obtained a reduction up to 30% in chloride ion penetration, which could increase up to 34% the structure service life (130).…”
Section: Service Life Improvements and Life Cycle Analysismentioning
confidence: 96%
“…Water tightness recovery may produce a reduction in the rate of deterioration of concrete and the reinforcement, and to produce an increase in the service life of the structure. Only a few studies are quantifying the improvements in durability and service life, such as (129,130). However, in the opinion of the authors, this is a key point, and improvements in terms of long-term behaviour need to be investigated to verify if the extension of service life produced by self-healing is worth the money inversion.…”
Section: D) What Type Of Recovery?mentioning
confidence: 99%